ALGORITHM FOR COMPETITIVE SELECTION OF CANDIDATES FOR ADMISSION TO THE UNIVERSITY FOR THE SECOND AND SUBSEQUENT YEARS OF STUDY TO THE CONDITION THAT THE SET OF ORDERED PRIORITY AREAS FOR THE PREPARATION OF THE STATEMENT - Oleg V. Ovchinkin; Aleksey I. Pykhtin (Открытое образование (Москва), 2016)
In this paper the problem is formalized competitive selection and admission to the following courses 2 and the example of the admission campaign in Southwest State University, an algorithm of solving the problem.